Sosialisasi Pemanfaatan Plagiarism Software berupa Turnitin pada Mahasiswa Tingkat Akhir Jurusan Tadris Bahasa Inggris, Fakultas Ilmu Tarbiyah dan Keguruan IAIN Sultan Amai Gorontalo - Hasan, Jhems Richard; Habibie, Alvons (Madani: Jurnal Pengabdian Ilmiah, 2024)
Examination of plagiarism actions towards scientific writing results, in line with the current technological advancements, cannot be denied. There are many checking tools available, whether through applications or web-based software. One of the familiar and widely used software is Turnitin. Therefore, the research team deemed it necessary to delve deeper and provide an understanding of the utilization of Turnitin software to students, especially in thesis writing. This study aims to introduce the use of Turnitin software as a similarity detection application in scientific writing, particularly in thesis works for final-year students in the English Language Teaching Department at IAIN Sultan Amai Gorontalo. The study involved 27 students. The utilization socialization model was conducted face-to-face. The results of this research show an improvement in understanding the utilization of Turnitin in the process of checking scientific writing, particularly in students' thesis works. This is evidenced by the difference in the level of understanding of Turnitin before and after socialization, which is quite significant at 35 percent. Such socialization needs to be carried out extensively to ensure that awareness of plagiarism actions and the utilization of Turnitin among students at IAIN Sultan Amai Gorontalo spreads evenly. Keywords: Plagiarism Checker; Utilization Socialization; Turnitin; Scientific Writing.